Economic Protective Strategy in Building Pesantren Independence: A Case Study of Pesantren Misbahul Ulum, Aceh, Indonesia - Muhammad Anggung Manumanoso Prasetyo; M. Syukri Rizki Hamdalah; Amila Shaliha; Razeev Khan (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2026)
This study identifies and develops a model of economic protective strategy aimed at enhancing the institutional independence of Islamic boarding schools (pesantren), using Pesantren Misbahul Ulum (PMMU) in Aceh, Indonesia, as an empirical case. Employing a qualitative, descriptive single-case design, the research involved seven purposively selected key informants, including the institutional leader, vice-leaders, and senior staff. Data were collected through semi structured in-depth interviews, participant observation, and documentary analysis, and analyzed using the Miles and Huberman interactive model, with source triangulation and member checking to ensure trustworthiness. The findings reveal four integrated protective dimensions: collective entrepreneurial leadership rooted in Islamic democratic governance (shura); innovation management anchored in prophetic principles; trust-based institutional capital as a primary economic resource; and the incremental development of an alumni-led entrepreneurial ecosystem. This study contributes the Protective Economic Strategy (PES) Model, a four component framework that synthesizes Islamic entrepreneurship, social capital, and institutional economics in an empirically grounded configuration, incorporating theological-normative trust capital as a functional analytic element. The model offers a replicable capacity-building pathway toward financial autonomy for pesantren in Indonesia and other Muslim-majority contexts. Future research should quantitatively validate the PES Model across multiple pesantren and assess its applicability to other value-based educational institutions.